Molecular identification of Cryptosporidium, Giardia, and Blastocystis from stray and household cats and cat owners in Tehran, Iran - Poorya Karimi; Soheila Shafaghi-Sisi; Ahmad Reza Meamar; Elham Razmjou (Scientific Reports, 2023)
Abstract Cryptosporidiosis, giardiasis, and blastocystosis are among the most important parasitic diseases common between humans and cats. In addition, there are concerns about the possible transmission of zoonotic parasites from infected cats to humans. Hence, we investigated the molecular epidemiology of Cryptosporidium spp., Giardia duodenalis, and Blastocystis sp. in stray and household cats and cat owners. Our study was performed on 132, 33, and 33 fecal samples of stray and household cats, as well as cat owners in Tehran, Iran. Cryptosporidium spp. was identified using a nested PCR targeting the small subunit ribosomal RNA gene (SSU rRNA) and sequencing the internal amplified fragments. Furthermore, to perform multilocus genotyping of G. duodenalis, the ß-giardin (bg), glutamate dehydrogenase (gdh), and triosephosphate isomerase (tpi) genes were amplified to assess the DNA of G. duodenalis in the fecal samples of cats and cat owners. In addition, Blastocystis was detected by targeting the SSU rRNA gene, and the subtypes of Blastocystis were determined via the sequencing of amplicons. Cryptosporidium felis and Cryptosporidium canis were detected in seven stray cats (5.3%) and one household cat (3%). The bg gene of G. duodenalis was amplified and successfully sequenced in two (1.5%) stray cats and revealed assemblages F and B of G. duodenalis. Sequencing and phylogenic analysis of SSU rRNA gene nucleotide sequences of Blastocystis detected ST5 and ST10 in stray cats (1.5%), ST1 in household cats (9.1%), and ST1, ST2, ST3, and ST7 in owners (30.3%). The low prevalence of Cryptosporidium, Giardia and Blastocystis in cats and the presence of species/assemblages/subtypes with limited zoonotic potential indicate that cats had a minor role in their owners' infection in the investigated population. However, the presence of zoonotic protozoa in cats suggests the necessity of special attention to high-risk individuals during close contact with cats. Therefore, it is recommended that veterinarians, physicians, and urban managers plan to prevent, control, or treat these parasites to help the urban community live healthily alongside cats.